Sargassum plagiophyllum Ethanolic Extract Enhances Wound Healing by Modulating FAK/Src/Akt/p38 and Rac1 Signaling in Keratinocytes HaCaT Cells - Furoida Moolsup; Wanida Sukketsiri; Wipawadee Sianglum; Jirawat Saetan; Nattakanwadee Khumpirapang; Supita Tanasawet (Advances in Pharmacological and Pharmaceutical Sciences)
Recently, seaweed extracts have been found to have potential in skin benefits. This study, therefore, aimed to explore phytochemical analysis, antimicrobial, antioxidant, and wound healing properties of brown seaweed Sargassum plagiophyllym ethanolic extract (SPEE) on human skin keratinocyte HaCaT cells and the possible mechanism involved. Our results indicated that SPEE contained flavonoid, phenolic, and carotenoid as the major active constituents. The HPLC chromatogram revealed C-phycocyanin and fucoidan presented in SPEE. SPEE demonstrated the antioxidant capability and significantly reduced wound space at 24 and 48 h in wound-healing assay. Treatment with SPEE (50 and 100 μg/mL) increased FAK and Src phosphorylation in western blotting. Moreover, SPEE also upregulated Akt and p38 MAPK phosphorylation but not ERK1/2. SPEE increased Rac1 protein expression. Interestingly, hyaluronan synthase (HAS1 and HAS2) as well as collagen type I and elastin were also significantly upregulated when compared with the control upon exposure to SPEE. In conclusion, our data suggested that SPEE promotes cutaneous wound healing by regulating FAK/Src-mediated Akt, p38 MAPK, and Rac1 signaling. These findings suggest the potential use of SPEE for skin wound treatment.